2014
DOI: 10.1007/s00705-014-2301-2
|View full text |Cite
|
Sign up to set email alerts
|

High levels of virus replication and an intense inflammatory response contribute to the severe pathology in lymphoid tissues caused by Newcastle disease virus genotype VIId

Abstract: Some strains of Newcastle disease virus (NDV) genotype VIId cause more-severe tissue damage in lymphoid organs compared to other virulent strains. In this study, we aim to define the mechanism of this distinct pathological manifestation of genotype VII viruses. Pathology, virus replication, and the innate immune response in lymphoid tissues of chickens infected with two genotype VIId NDV strains (JS5/05 and JS3/05), genotype IX NDV F48E8 and genotype IV NDV Herts/33, were compared. Histopathologic examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 22 publications
11
50
1
Order By: Relevance
“…NDV infection induced strong pro-inflammatory responses that played an important role in viral pathogenesis. The IL-2/6/1β and IFN-β mRNA expression levels were increased in the oviductal tissues of NDV-infected hens; our data are consistent with previous findings [912]. The expression of the IL-2 gene in the peripheral blood of F48E9 NDV-infected chickens in a previous study fluctuated and did not exhibit a significant difference compared with the control group during the experimental period [26].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…NDV infection induced strong pro-inflammatory responses that played an important role in viral pathogenesis. The IL-2/6/1β and IFN-β mRNA expression levels were increased in the oviductal tissues of NDV-infected hens; our data are consistent with previous findings [912]. The expression of the IL-2 gene in the peripheral blood of F48E9 NDV-infected chickens in a previous study fluctuated and did not exhibit a significant difference compared with the control group during the experimental period [26].…”
Section: Discussionsupporting
confidence: 92%
“…IFN-α belongs to the type I interferon family and can be produced in most cells after virus infection, whereupon it localizes to the site of viral infection and inhibits viral replication. In this study, IFN-α experienced a decline in the magnum of hen oviducts 3 dpi; the same phenomenon was reported in another study that demonstrated that the expression of IFN-α experienced a sharp decline in the peripheral blood of F48E9 NDV-infected chicken 7 dpi [12], which might contribute to rapid viral replication. The highest levels of expression of the examined genes corresponded with the significant clinical signs and the inflammatory responses in the oviductal tissues.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Genotype VII viruses within class II that merged decades ago are now the major genotype of virus that are circulating in different countries including China [3]. The genome of NDV is approximately 15kb and encodes 6 structural proteins including nucleoprotein (NP), phosphoprotein (P), matrix protein (M), fusion protein (F), hemagglutinin-neuraminidase (HN), the large protein (L), and two nonstructual proteins V and W. The NDV strains can be grouped as highly (velogenic), moderately (mesogenic), and weakly pathogenic (lentogenic) pathotypes according to cleavage site of fusion (F) gene which works as a virulence-determine gene [4].…”
Section: Introductionmentioning
confidence: 99%
“…21 Increased virus replication and a greater inflammatory response within lymphoid tissues has been associated with increased pathogenicity of velogenic ND viruses. 164 The results of our study indicate that the low pathogenicity of the Meredith/02 virus must be attributed to regions of the viral genome other than the F protein cleavage site, given that the cleavage site contains a virulent motif. Studies using reverse genetics have also indicated that regions of the NDV genome other than the F protein cleavage site may also contribute significantly to pathogenicity.…”
Section: Discussionmentioning
confidence: 70%